Fabrication of highly stable and sensitive electrochemical sensor from hemoglobin–Au nanocomposites and its analytical applications. Issue 68 (5th September 2017) - Wu, Weiping; Fang, Yuting; Zhu, Chenchen; Chen, Shiyu; Li, Ting; Wu, Lei; Bao, Ning; Liu, Yang; Gu, Haiying
Abstract : Hemoglobin–Au nanocomposites fabrication of highly stable and sensitive electrochemical sensor. Abstract : To improve electron transfer, a combination of electroactive hemoglobin (Hb) and Au nanoparticles (Au NPs) was designed to obtain nanocomposites (NCs). Cyclic voltammetry and redox probe characterization showed that Hb–Au NCs incorporating the layer-by-layer technique to improve the ration of electroactive Hb, showed a better conjugated structure, lower standard entropy, and faster electron transfer. Au entrapped in Hb on the glassy carbon electrode (GCE) also exhibited a wider linear range, and excellent reproducibility and recovery for analytical applications of hydrogen peroxide, oxygen, and trichloroacetic acid. Therefore, our research could potentially become a promising alternative by combining bioactive molecules with nanoparticles, and broaden the applications of mediator-free biosensors.